2019
DOI: 10.3390/coatings10010008
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Silk Fibers by PDGF and Bioceramics for Bone Tissue Regeneration

Abstract: Bone regeneration is a complex, well-organized physiological process of bone formation observed during normal fracture healing and involved in continuous remodeling throughout adult life. An ideal medical device for bone regeneration requires interconnected pores within the device to allow for penetration of blood vessels and cells, enabling material biodegradation and bone ingrowth. Additional mandatory characteristics include an excellent resorption rate, a 3D structure similar to natural bone, biocompatibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…When active substances (synthetic pharmaceutics or natural compounds) cannot be used alone, composite materials based on different polymers can be developed for enhancing their properties. Due to their effective biocompatibility and biodegradability, natural polymers used for coatings in medical devices, such as chitosan, starch, alginate, collagen, gelatin, or silk, were reported by different authors [45][46][47]. Moreover, different studies revealed that the construction of such medical devices in the form of a layer-by-layer coating can generate multi-component coatings with an increased ability to regulate the release of active substances [48][49][50].…”
Section: Coating Materials For Biomedical Applicationsmentioning
confidence: 99%
“…When active substances (synthetic pharmaceutics or natural compounds) cannot be used alone, composite materials based on different polymers can be developed for enhancing their properties. Due to their effective biocompatibility and biodegradability, natural polymers used for coatings in medical devices, such as chitosan, starch, alginate, collagen, gelatin, or silk, were reported by different authors [45][46][47]. Moreover, different studies revealed that the construction of such medical devices in the form of a layer-by-layer coating can generate multi-component coatings with an increased ability to regulate the release of active substances [48][49][50].…”
Section: Coating Materials For Biomedical Applicationsmentioning
confidence: 99%
“…Wöltje and coworkers explored the genetic alteration of silkworms to obtain silk fibers functionalized with human platelet-derived growth factors [4]. The fibers were also modified with bioceramics and assembled into a 3D textile implant to achieve high levels of osteoconductivity.…”
Section: Surfaces Modification and Analysis For Innovative Biomaterialsmentioning
confidence: 99%
“…In the last century, an intense research effort has been devoted to the reinforcement of bioceramics for different applications. In this respect, various approaches have been proposed, including modified sintering treatments [51][52][53], combination with polymeric phases to produce composites [49,54,55], the addition of fibers or the development of additive manufacturing as a 3D technique to prepare complex-shaped bioceramic structures [34,[56][57][58][59][60]. A major approach to this purpose is the addition of ceramic particles, whiskers, and fibers to the ceramic matrix to improve the fracture toughness [61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%